2000
DOI: 10.4049/jimmunol.164.3.1355
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase as a Mediator of TNF-Induced NF-κB Activation

Abstract: The activation of transcription factor NF-κB by TNF involves the stimulation of a novel signaling cascade. In this paper we show that phosphatidylinositol 3-kinase (PI 3-kinase) may play a pivotal role in TNF-mediated activation of NF-κB-dependent genes. Consistent with its involvement in TNF signaling, PI 3-kinase activities in HepG2 and U937 cells can be stimulated by TNF in a rapid but transient manner through a mechanism that may involve its association with the insulin receptor substrate-1. A dominant-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
112
2
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 47 publications
8
112
2
2
Order By: Relevance
“…PI3K regulates multiple pathways monocyte activity [11,[15][16][17][18][19][20][21][22][23][24][25][26][27]. PI3K is necessary for monocyte survival, since inhibition of PI3K and subsequently Akt resulted in cell death even in the presence of LPS or TNF- § .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K regulates multiple pathways monocyte activity [11,[15][16][17][18][19][20][21][22][23][24][25][26][27]. PI3K is necessary for monocyte survival, since inhibition of PI3K and subsequently Akt resulted in cell death even in the presence of LPS or TNF- § .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that Akt may inhibit apoptosis mediated by the death receptor or mitochondrial pathways, through the phosphorylation and inactivation of the pro-apoptotic Bcl-2 family protein Bad, caspase 9 or the forkhead transcription factor [12]. Furthermore, Akt was also shown to activate NF-‹ B and suppress apoptosis through an unknown mechanism [16], although recent investigations suggested that NK-‹ B regulation by PI3K/Akt pathway may be cell type specific [28]. Thus, the mechanism by which the mitochondrial apoptotic pathway may be regulated by PI3K in monocytes is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent study demonstrated that PI3K-Akt may play a pivotal role in cytokine-induced transcriptional activation of NF-kB-and AP-1-dependent gene expression. 8,9 The active form of vitamin D 3 , 1a,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), influences the expression of various genes, whose products are involved in calcium homeostasis, cell differentiation, and regulation of the immune response. 10 The expression of these genes is mediated by binding to its nuclear vitamin D receptor (VDR), a transcription factor, which dimerizes with either itself or other nuclear receptors, such as the retinoid X receptor (RXR).…”
mentioning
confidence: 99%
“…In recent studies, Akt has been identified as a part of the TNF-␣ signaling pathway that leads to inflammatory responses and inhibition of apoptosis in vitro (Nidai Ozes et al, 1999;Pastorino et al, 1999;Reddy et al, 2000). A connection between membrane depolarization and phosphatidylinositol 3-kinase (PI3-K)-dependent Akt phosphorylation was found in cultured rat sympathetic neurons (Vaillant et al, 1999).…”
mentioning
confidence: 99%